1989
DOI: 10.1111/j.1399-3054.1989.tb05484.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes induced by accelerated aging in sunflower seeds. I. Lipid peroxidation and membrane damage

Abstract: 1989, Biochemical changes induced by accelerated aging in sunflower seeds. 1. Lipid peroxidation and membrane damage, -Physiol. Plant, 76; 591-597.When stored at 42°C and 100% relative humidity for 1 to 8 days, sunflower seeds (Heliatithus antiuus L, cv. Rodeo) aged prematurely and lost 25' }<) of their initial viability. A ten-fold increase in conjugated dienes as well as a decrease of unsaturated fatty acids in diacylglycerol and polar lipids fractions were observed after 8 days of accelerated aging, demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 20 publications
(15 reference statements)
8
48
2
2
Order By: Relevance
“…Results are the means of three independents assays; bars correspond to Ϯ standard error. Gidrol et al (1989) and Lehner et al (2007) did not find any increase in this compound during the accelerated aging of sunflower or wheat seeds. On the contrary, Goel et al (2003) or Kibinza et al (2006), for example, demonstrated that MDA accumulated during seed aging.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results are the means of three independents assays; bars correspond to Ϯ standard error. Gidrol et al (1989) and Lehner et al (2007) did not find any increase in this compound during the accelerated aging of sunflower or wheat seeds. On the contrary, Goel et al (2003) or Kibinza et al (2006), for example, demonstrated that MDA accumulated during seed aging.…”
Section: Discussionmentioning
confidence: 95%
“…In the seeds from the Marchouche variety, accelerated aging induced a 9.8% decrease in the proportion of TAG accompanied by a 6.5% increase in the proportions of FFA (Figure 3). No significant variation was Gidrol et al (1989) and Corbineau et al (2002) obtained with sunflower seeds. Unsaturated fatty acid and phosphatidylcholine contents were particularly low.…”
Section: Ouzouline N Tahani C Demandre a El Amrani G Benhamentioning
confidence: 99%
“…The per cent increase over control was 17 and 34%, respectively. Gidrol (1989) reported that the decreased activity of peroxidase and catalase was due to accumulation of H 2 O 2, as seeds neutralized free radicals and this accumulation of hydrogen peroxide itself was detrimental to seeds. Depletion of antioxidant enzyme activities was also observed during seed ageing in cotton (Goel et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…those involved in cellular respiration are susceptible to oxidative modifications (Møller 2001). It is thought that damage of mitochondrial membranes increases their permeability and leakage of lipid peroxides to cytoplasm (Gidrol et al 1989). It is suggested that these compounds may participate in signal transduction between mitochondria and other organelles and nucleus.…”
Section: Discussionmentioning
confidence: 99%